ANALISIS STRATEGI PENGEMBANGAN UMKM NARA HANDY CRAFT DALAM MENINGKATKAN DAYA SAING PRODUK LOKAL - Milyin Niam Sawmy; Febri Ariyantiningsih; Meiliana Dian Lestari; Yunita Maqqiyatul; Riski Maulana (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the development strategies of handicraft Micro, Small, and Medium Enterprises (MSMEs) in enhancing the competitiveness of local products. Handicraft MSMEs play an important role in the local economy, particularly in creating employment opportunities and preserving local cultural values. However, these enterprises still face various challenges, such as limited capital, marketing constraints, lack of product innovation, and low utilization of digital technology. This research uses a descriptive qualitative method, with data collected through observation, interviews, and literature review. The results indicate that the development strategies of handicraft MSMEs can be implemented through improving product quality, design innovation, utilization of digital marketing, strengthening branding, and support from the government and related institutions. By implementing appropriate strategies, nara handi craft MSMEs are expected to improve the competitiveness of local products in broader markets, both nationally and internationall